Language self-learner - Zeki, Akram M.; Nooh, Athifah Nafhah; Hassan Abdalla Hashim, Aisha (IIUM Press, 2011)
Multimedia courseware is a software developed for educational purposes. Nowadays, learning to speak more than two languages gives one a good edge over others. However, the main objective of this project is to create a courseware that helps user to learn three different languages at one time. This project is developed by improving the limitations of existing products. This project is basically a language self-learner that consists of Mandarin, Japanese, and Korean languages. English will be provided to assist the user. This product will provide the visual, Kanji, Romaji and audio of the word. So, users can actually hear the correct pronunciation of the word. At the same time, users can learn to write the Kanji of the word. Therefore, users will get many benefits by using this product.